Analisis Kesulitan Belajar Mahasiswa Pada Mata Kuliah Ekonomi Makro Di Tinjau Dari Persepsi Mahasiswa Tentang Keterampilan Mengajar Dosen dan Partisipasi dalam Pembelajaran Pada Mahasiswa Pendidikan Akuntansi UniversitasMuhammadiyah Surakarta Angkatan 2015 - Hidayat, Arif, Drs. Djoko Suwandi, S.E., M.Pd (2016)
This research aims to determine: 1) The influence perceptions about skills lecture of teaching to student learning difficulties, 2) The influence participation in learning to student learning difficulties, 3) The influence perceptions about skills lecture of teaching and participation in learning to students learning difficulties. This study was descriptive quantitative. The study took place at the University of Muhammadiyah Surakarta FKIP Accounting. The entire student population FKIP 2015 Accounting forces who are taking courses macro economic, totaling 251 students. Samples taken as many as 146 to nonprobability sampling techniques accidental way. Data obtained through the documentation and questionnaire. The data analysis technique used is multiple linear regression analysis, t test, f test, and contribution relative and effective. The results of the regression analysis obtained regression equation: Y = 7.894 + 0,183X1 + 0,406X2. Conclusion are: 1) Perceptions about teaching skills significantly influence student learning difficulties. This is based on test t known fact that thitung = 6.069 > ttable = 1.977 at the 5% significance value with contribution relative 38,07% and contribution efektive 21.6%. 2) Participation in learning significantly influence student learning difficulties. This is based on test t known fact that thitung = 8.595 > ttable = 1.977 at the 5% significance value with contribution relative 61.93% and contribution efektive 35.3%. 3) Perceptions about teaching skills and participation in learning significantly influence student learning difficulties. This is based on test f known that Fhitung = 94.516 > Ftable = 3.059 at the 5% significance value 4) The coefficient of determination (R2) of 0.569 indicates that the influence of the perception of the teaching skills of faculty and participation in learning for learning difficulties students is 56.9 % while the rest influenced by other variables.